The Impact of the Moral Foundations Arguments on Early Adolescents - Stastna, Kamila (Wydział Filozoficzny, Uniwersytet im. Adama Mickiewicza w Poznaniu, 2021)
The empirical research reported in this article is based on the Moral Foundations Theory proposed by J. Haidt. Objectives. The author examines the impact of moral foundations arguments on early adolescents’ moral judgments regarding violating moral rules and explores gender-related differences between moral foundations preferences. Method. The effect of moral foundations arguments was measured by a newly developed meta-ethical position test (MEPT). The MEPT consists of a pretest questionnaire, treatment by moral foundations arguments, and a posttest questionnaire. The sample contained 178 early adolescents from the Czech Republic (84 females and 94 males). The influence of the moral foundations arguments was analyzed by comparing the pretest with the posttest. Results. 91% of teenagers changed their moral judgment due to confrontations with the moral foundations arguments. A Wilcoxon signed-rank test found that the moral foundations arguments were significantly relevant, since the P-value was lower than 0.001. The Mann-Whitney U test revealed the importance of the gender aspect: P-value care equals 0.01 and liberty 0.01. Girls have a preference for care foundation (21% more than boys), while boys tended to liberty (27 % more than girls). It seems that moral foundations arguments strongly change early adolescents’ moral judgments and can be practically applied as a valuable platform for early adolescents’ moral development.
Keywords: Moral Foundations Theory; moral judgment; moral competence; moral foundations argument; gender; moral development